COMPARATIVE EFFECTS OF DECLINE PUSH-UPS VS. STANDARD PUSH-UPS ON ARM MUSCLE POWER AND OVERHEAD VOLLEYBALL SERVE ABILITY IN MALE ATHLETES: A STUDY OF SEMBADA WIJAYA VC CLUB - Selamat S Naibaho (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
Volleyball is a sport played by men or women played by 2 teams where on each court is separated by a net. The purpose of this game is to drop the ball through the net and enter the opponent's field of service starting from the back line of the field, and the ball falls through the net and enters the opponent's field. This research was carried out at the training location, namely the field of the Sembada Wijaya VC Club Medan. Jalan Bunga Wiwijaya Kesuma, Padang Bulan Pasar III Medan. The results of the study The Difference in the Effect of Decline Push Up and Standard Push Up Exercises on Arm Muscle Power and Volleyball Top Service Ability, There was a significant effect of decline push up exercises on the increase in arm muscle power, the statistical calculation value of 36.537 which can be expressed by ttable (n=5 df= n-k.5 -) compared with the value of 3,182 results, There is a significant effect of standard push up exercises on increasing arm muscle power, decline push up exercises are significantly better than standard push up exercises on increasing arm muscle power with the results of statistical calculations displaying a tcal value of 25.84 which can be expressed as a ttable value (n=5 df= n-k-5) compared to 3,182 Results of Volleyball Service Ability in Male Athletes Sembada Jaya VC Medan City